The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/ijc.1349
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of hepatocyte growth factor activator inhibitor type-2/placental bikunin (HAI-2/PB) in human glioblastomas: Implication for anti-invasive role of HAI-2/PB in glioblastoma cells

Abstract: Hepatocyte growth factor activator inhibitor type-2/placental bikunin (HAI-2/PB) is a serine proteinase inhibitor that contains 2 Kunitz-domains and a presumed transmembrane domain. It has broad inhibitory spectra against various serine proteinases showing potent inhibitory activities not only to hepatocyte growth factor activator but also to plasmin, trypsin and kallikreins. In this study, we investigated the expression of HAI-2/PB in human gliomas in viv o and the effects of HAI-2/PB on the fibrinolytic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 24 publications
(34 reference statements)
2
24
0
Order By: Relevance
“…7C and D). Similar to a previous report (Hamasuna et al, 2001), forced re-expression of SPINT2 also reduced cell mobility in U87G cells as accessed by artificial wound healing analysis (data not shown).…”
Section: Resultssupporting
confidence: 90%
“…7C and D). Similar to a previous report (Hamasuna et al, 2001), forced re-expression of SPINT2 also reduced cell mobility in U87G cells as accessed by artificial wound healing analysis (data not shown).…”
Section: Resultssupporting
confidence: 90%
“…The disturbed methylation status in the promoter region of the SPINT2/HAI-2 gene highlighted its potential use as an emerging anticancer agent (Hamasuna et al, 2001). Kobayashi et al (2004) reported that oral SPINT2/HAI-2 therapy reduced tumor load in a nude mouse model and in human ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it inhibits the formation of active HGF by inhibiting the action of the HGF activator (Tung et al, 2009). It is recognized as a tumor suppressor gene and its underexpression has been reported in cancers, such as breast cancer (Parr et al, 2004) and glioblastoma (Hamasuna et al, 2001;Schuster et al, 2003). Morris et al (2005) have demonstrated promoter region hypermethylation of SPINT2/HAI-2 in renal cell carcinoma cell lines and primary tumors; however, the role in HCC is still under research.…”
Section: Introductionmentioning
confidence: 96%
“…Intestinal deletion of endogenous HAI-1 augments Wnt signaling in Apc Min/+ mice, both in tumors and in normal mucosa, and enhances intestinal tumor formation [72], confirming that HAI-1 has tumor suppressor properties. Accordingly, reduced expression of HAIs is associated with advanced disease and poor outcome in cancer patients [72,73,74,75,76,77,78]. Small molecule inhibitors of HGFA and antibodies neutralizing HGFA and matriptase have been developed [79] as potential therapeutic agents.…”
Section: Hgf/met Signaling In the Tumor Microenvironmentmentioning
confidence: 99%